Scientific production in Scopus of the public specialized health institutes in Peru, 2010-2022 - Fernandez-Guzman, Daniel (2023)
Objective: To evaluate the scientific production of Peruvian health institutes in Scopus, 2010-2022. Methods: We conducted a Bibliometric study in Scopus during September 2022, in 14 public specialized health institutes of Peru. We included original studies with at least one author from one of the institutes. Results: The institutes included published between 0 and 347 original articles (H-index between 0 and 51). The institutes in the city of Lima were the ones with the highest production. In the seven institutes with the highest production, the percentage of articles with a corresponding author from the institute evaluated ranged from 22.3% to 36.7%, and the percentage of studies that reported being financed by the institute ranged from 0% to 11.6%. Conclusion: The scientific production of the evaluated institutes was heterogeneous, with a predominance of those located in Lima. The institutes rarely participated in the financing of the published studies.